MOFs-Derived Strategy and Ternary Alloys Regulation in Flower-Like Magnetic-Carbon Microspheres with Broadband Electromagnetic Wave Absorption - Huang, Mengqiu; Li, Bangxin; Qian, Yuetong; Wang, Lei; Zhang, Huibin; Yang, Chendi; Rao, Longjun; Zhou, Gang; Liang, Chongyun; Che, Renchao (Nano-Micro Letters, 2024)
Broadband electromagnetic (EM) wave absorption materials play an important role in military stealth and health protection. Herein, metal–organic frameworks (MOFs)-derived magnetic-carbon CoNiM@C (M = Cu, Zn, Fe, Mn) microspheres are fabricated, which exhibit flower-like nano–microstructure with tunable EM response capacity. Based on the MOFs-derived CoNi@C microsphere, the adjacent third element is introduced into magnetic CoNi alloy to enhance EM wave absorption performance. In term of broadband absorption, the order of efficient absorption bandwidth (EAB) value is Mn > Fe = Zn > Cu in the CoNiM@C microspheres. Therefore, MOFs-derived flower-like CoNiMn@C microspheres hold outstanding broadband absorption and the EAB can reach up to 5.8 GHz (covering 12.2–18 GHz at 2.0 mm thickness). Besides, off-axis electron holography and computational simulations are applied to elucidate the inherent dielectric dissipation and magnetic loss. Rich heterointerfaces in CoNiMn@C promote the aggregation of the negative/positive charges at the contacting region, forming interfacial polarization. The graphitized carbon layer catalyzed by the magnetic CoNiMn core offered the electron mobility path, boosting the conductive loss. Equally importantly, magnetic coupling is observed in the CoNiMn@C to strengthen the magnetic responding behaviors. This study provides a new guide to build broadband EM absorption by regulating the ternary magnetic alloy. Highlights: 1 Metal–organic frameworks-derived CoNiM@C (M = Cu, Zn, Fe, Mn) microspheres were successfully fabricated with custom-built magnetic alloy-carbon heterogeneous interfaces. 2 Flower-like CoNiMn@C microspheres achieve broadband electromagnetic wave absorption with effective absorption bandwidth of 5.8 GHz at only 2.0 mm thickness. 3 Visual interface charge distribution and hierarchical magnetic coupling were observed to elucidate the electromagnetic energy absorption mechanism.